PENGARUH BOARD GENDER DIVERSITY DAN KINERJA KEUANGAN TERHADAP KINERJA ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) - Putri, Alika Shahrani; Restuti, Mitha Dwi (E-Jurnal Akuntansi TSM, 2025)
This study investigates the influence of board gender diversity and corporate financial performance on Environmental, Social, and Governance (ESG) performance among publicly listed firms in Indonesia. Drawing on a sample of 323 firm-year observations from the Indonesia Stock Exchange for the period 2014–2022, this study employs multiple linear regression analysis to test the proposed hypotheses. The results indicate that board gender diversity does not have a significant impact on ESG performance, potentially due to the limited presence of women in boardrooms, which restricts their strategic influence and renders their roles largely symbolic. In contrast, corporate financial performance is found to negatively affect ESG performance, suggesting that firms tend to prioritize short-term profitability over sustainable practices. These findings highlight the challenges of aligning corporate governance and financial incentives with long-term ESG objectives in emerging market contexts.